2002
DOI: 10.1074/jbc.m201613200
|View full text |Cite
|
Sign up to set email alerts
|

Serial Triggering of T Cell Receptors Results in Incremental Accumulation of Signaling Intermediates

Abstract: Triggering of the T cell receptor (TCR) leads to the production of intracellular intermediates with half-life of a few minutes. Signaling kinetics of events originating from serial TCR triggering and its relation to antigen dose was investigated. In this study we documented incremental accumulation of short-lived intermediates of the extracellular signal-regulated kinase (ERK) family, produced during successive TCR triggering. The rate and extent of the intermediate accumulation are essentially determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In contrast, the Th2 cytokine IL-5 approached its plateau at 1 ng/ml SEB, and further increases in the SEB dose enhanced cytokine secretion only marginally. This pattern of dose-dependent cytokine responses is consistent with earlier reports by us (26) and others (1,(27)(28)(29) for both SEB and other Ags. Of note, while the absolute levels of cytokine secretion varied up to 10-fold between different donors, the same pattern was evident in each case.…”
Section: Differentiation Of Cd4supporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, the Th2 cytokine IL-5 approached its plateau at 1 ng/ml SEB, and further increases in the SEB dose enhanced cytokine secretion only marginally. This pattern of dose-dependent cytokine responses is consistent with earlier reports by us (26) and others (1,(27)(28)(29) for both SEB and other Ags. Of note, while the absolute levels of cytokine secretion varied up to 10-fold between different donors, the same pattern was evident in each case.…”
Section: Differentiation Of Cd4supporting
confidence: 81%
“…Thus, while both Th1 and Th2 cytokines are expressed simultaneously, low doses of stimuli primarily induced Th2 cytokines (IL-4 and IL-5), with low to undetectable levels of Th1 cytokines (IL-2 and IFN-␥), whereas priming with higher doses of stimuli favored increased production of Th1 cytokines. The Th1 skewing was correlated with the induction of ERK phosphorylation (26), and blocking this phosphorylation event specifically blocks the Th1 response (38). The observed effects of PP14 on early cytokine output can be readily understood within this framework.…”
Section: Discussionmentioning
confidence: 99%
“…5D). Such temporal differences in ERK activation have been reported, and the authors suggested that this phenomenon was due to the difference in TCR occupancy (42). As shown in Fig.…”
Section: Expression Of B-raf Proteins Inmentioning
confidence: 73%
“…There exist numerous models of TCR triggering and their modifications, 2 including, but not limited to, a kinetic proofreading model, 280,296,298,[302][303][304][305][306] serial triggering model, 162,[307][308][309][310] serial encounter model, 311 conformational models, 126,165,[193][194][195]258,[312][313][314][315][316][317][318][319] Figure 8 (See previous page). SCHOOL model of T cell receptor (TCr) signaling.…”
Section: School Model Of T Cell Receptor Signalingmentioning
confidence: 99%